Self-Tuning PID-Genetic Algorithm Controller for Steam Drum Boiler Water Level Control System - Mohamad Abdul Hady; Mohamad Yusuf; Ali Fatoni; Imam Arifin (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
A control system with uncertainty or unpredictable disturbance needs more effort to be controlled. A conventional PID Controller is the most popular method used in industries. It was tuned and adjusted by the designer, and it has fixed parameters during operation. However, the disturbance effect causes the desired system performance unreachable. By using a self-tuning controller, the problem should be tackled. In this paper, the PID-Genetic Algorithm (PID-GA) controller was proposed and tested with the steam drum water level control system of a steam power plant. Variation in power load causes noisy water level characteristics and should be maintained at + 0.4 meters from the setpoint to prevent the power plant trip. From the simulation, PID-GA can reduce disturbance of the minimum, nominal, and maximum load with perturbation peaks 0.18 m, 0.22 m, and 0.26 m respectively.Keywords: genetic algorithm, NWL, PID-GA, steam drum, steam power plant.